2012
DOI: 10.1016/j.ijgo.2012.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrapartum outcome among immigrant women from Ethiopia and the general obstetric population in Israel

Abstract: Although prepartum and intrapartum care are standardized, Ethiopian women had a less favorable intrapartum outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Migrant Ethiopian women gain little weight during pregnancy, potentially for similar reasons (Salim et al . ). These women have higher incidences of emergency Caesareans and interventions during labour, pre‐eclampsia, early postpartum haemorrhage, preterm and post‐term birth, stillbirth and small‐for‐gestational‐age babies (Salim et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Migrant Ethiopian women gain little weight during pregnancy, potentially for similar reasons (Salim et al . ). These women have higher incidences of emergency Caesareans and interventions during labour, pre‐eclampsia, early postpartum haemorrhage, preterm and post‐term birth, stillbirth and small‐for‐gestational‐age babies (Salim et al .…”
Section: Resultsmentioning
confidence: 97%
“…These women have higher incidences of emergency Caesareans and interventions during labour, pre‐eclampsia, early postpartum haemorrhage, preterm and post‐term birth, stillbirth and small‐for‐gestational‐age babies (Salim et al . , Merry et al . , Calderon‐Margalit et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite regional variations, few studies have reported variations in pre-eclampsia among immigrants to industrialised countries according to maternal birthplace or ethnic origin and almost none in eclampsia 1014. These studies were based on a single setting, such as a hospital,12,13 midwife practices,15 a city,10,11 or a province14 and used different definitions of the outcomes and migrant groups. Conclusions regarding disparities according to immigrants' maternal birthplace based on single-site studies may not be generalisable to other settings.…”
Section: Introductionmentioning
confidence: 99%
“…Australia is a multicultural country, with one of the highest CS rates globally, but there is little population‐based research on CS rates for immigrants in general and African immigrants in particular. Existing international studies have reported an overall higher CS risk for African immigrants, but it is unclear whether this higher risk is present for women without previous CS or differs by parity or by specific maternal country of origin. Therefore, we studied variations in first‐time caesarean birth, particularly unplanned CS in labour between Eastern African immigrants (Eritrea, Ethiopia, Somalia, Sudan) and Australian‐born women using the Victorian Perinatal Data Collection (VPDC).…”
Section: Introductionmentioning
confidence: 97%